Dermatologic alterations in nutritional anemias - Ruiz, Oscar (2006)
Objectives: To determine the frequency of anemia-related dermatological abnormalities and severity. Materials and Methods: A sample of 100 subjects older than 18 years with a diagnosis of nutritional anemia who were admitted at 2 de Mayo Hospital between January and November, 2004 was studied. In each subject we measured total CBC and serum iron, ferritin, folate, and cobalamin levels. Results: The type of anemia was iron deficiency in 45%, mixed anemia (iron deficiency and megaloblastic anemia) in 35%, and megaloblastic anemia in 20%. Dermatological abnormalities were pallor (100%), atrophic glossitis (81%), angular cheilitis (60%), koilonychia (33%), tinyblue sclera (30%), thinning hair (29%), thinning nails (29%); 75% of the cases were determined as having severe anemia. Conclusions: The nutritional anemia most frequently found was iron deficiency (45%). About 80% of subjects showed more than four dematological abnormalities: pallor, atrophic glossitis, angular cheilitis, koilonychia and tiny-blue sclera.